Deep eutectic solvent-based magnetic molecular nanomaterials coupled with fluorescent carbon dots as a new strategy to highly enrich and sensitively detect doxycycline in food matrices - Yanqiong Luo; Han Zhang; Jun Liu; Aleeza Jamil; Yujiao Hou; Qian Li; Min Zhao; Chunjie Zhao; Wenjing Li; Bo Hong (Food Chemistry: X)
The highly selective enrichment and sensitive detection of antibiotics in food are crucial for human health, environmental monitoring, and management. In this study, deep eutectic solvents (DESs) were used as eco–friendly functional monomers, a magnetic molecular nanomaterial (DES–MMIP) coupled with carbon dots (CDs) was developed as a sensitive fluorescent probe for the selective enrichment and detection of trace amounts of doxycycline (DOX). Under optimal conditions, the method exhibited good linearity within 0.5–50 μg·L−1, a low detection limit of 0.34 nM for DOX detection. Furthermore, the DES–MMIP displayed excellent reusability and storage stability. With responsive, excellent selectivity and an eco–friendly nature, the established method is successful in detecting DOX in food matrices, with an average spiked recovery of 87.5 %–97.8 %. This strategy of integrating CDs and DES–MMIP for DOX detection conforms to the green concept of environmental protection and provides a new material and research approach for efficient analysis of DOX in complex matrices.